Decision points [large type] - Bush, George W. (George Walker), 1946- (Random House Large Print, 2010)
Decision points is the memoir of America's 43rd president. George W. Bush offers a candid journey through the defining decisions of his life while writing about his flaws and mistakes, as well as his accomplishments.